KONSERVASI ENERGI DENGAN KENDALI SISTEM PEMOMPAAN AIR MENGGUNAKAN VARIABLE FREQUENCY DRIVE - Sofyar Sofyar (Al-Ulum, 2017)
In some forms, energy is the basic input to life. Energy is equally important to improve the quality of life. Energy conservation can help reduce the demand for energy globally and indirectly improve the environment by reducing the use of fossil fuels. Pumps in drinking water companies are used for processing and distributing water to consumers. Variable frequency drives offer efficient control for the centrifugal pump, which can save the electrical energy required for its operation.